2022
DOI: 10.1109/tii.2021.3054674
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Data-Driven Diagnosis of Incipient Interturn Short Circuit Fault in Field Winding of Salient Pole Synchronous Generators

Abstract: This paper examines if machine learning (ML) and signal processing can be used for on-line condition monitoring to reveal inter-turn short circuit fault (ITSC) in the field winding of salient pole synchronous generators (SPSG). This was done by creating several ML classifiers to detect ITSC faults. A data set for ML was built using power spectral density of the air gap magnetic field extracted by fast Fourier transform (FFT), discrete wavelet transform energies, and time series feature extraction based on scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Infrastructure project schedules can be characterized by investment and construction completion rate curves. Hence, Tsfresh and feature filtering methods are used to identify vital sequential features affecting power grid infrastructure planning from investment and construction completion rate curves (Ehya et al, 2022). Based on hypothesis testing, the feature filtering method is applied to evaluate the correlation between the project duration T and the sequential feature x extracted using the Tsfresh method.…”
Section: Feature Extraction Of Infrastructure Project Schedulesmentioning
confidence: 99%
“…Infrastructure project schedules can be characterized by investment and construction completion rate curves. Hence, Tsfresh and feature filtering methods are used to identify vital sequential features affecting power grid infrastructure planning from investment and construction completion rate curves (Ehya et al, 2022). Based on hypothesis testing, the feature filtering method is applied to evaluate the correlation between the project duration T and the sequential feature x extracted using the Tsfresh method.…”
Section: Feature Extraction Of Infrastructure Project Schedulesmentioning
confidence: 99%
“…Furthermore, the research of [90] using MFCC FE demonstrated that an MLP as a meta-classifier improved the overall performance of the models. In addition, [91] also used MLP as one of their meta-classifier. Thus, we employed an MLP as our metaclassifier.…”
Section: A Machine Learning Modelmentioning
confidence: 99%
“…For one thing, the feature extraction of CTO-LGC running log is implemented and performed by a Python package that is time series feature extraction on the basis of scalable hypothesis tests named as tsfresh [65], and the extracted features with tsfresh has been used for multiple types of tasks, for instance, classification, compression, forecasting, detection, recognition, and diagnosis [66][67][68][69][70]. For PSAC, the tsfresh package plays an important role in the deep learning data preparation process.…”
Section: Problem-oriented Lightweight Adaptive Deep Learningmentioning
confidence: 99%